Who Is Smart with Their Smartphones? Determinants of Smartphone Security Behavior - Knapova, Lenka; Kruzikova, Agata; Dedkova, Lenka; Smahel, David (Cyberpsychology, behavior and social networking, 2021)
Smartphones have recently become a major target for cybercriminals due to large amounts of sensitive data and credentials being stored on the devices. To protect themselves against cyberthreats, users can employ a range of security behaviors. Although research has largely focused on computer security, relatively little is known about personal smartphone security behavior. The goal of our study was to evaluate determinants of smartphone security behavior based on the combination of the Health Belief Model and Protection Motivation Theory. We extended the models by including the construct of general security orientation. We also developed a smartphone security behavior scale that measured various aspects of this behavior. The sample included 331 Czech Android smartphone users aged between 26 and 81 years who were not IT specialists by employment or education. Path analysis showed that individuals who perceived a potential smartphone security threat as more severe, had higher smartphone self-efficacy, and general orientation and interest in digital security, and less personal experience with a digital security incident reported more secure behavior on their smartphones. Perceived susceptibility to security threats and family and friends' previous experience with digital security incidents did not predict smartphone security behavior. General security orientation affected smartphone security behavior also indirectly through perceived severity. These findings have theoretical implications for the models and also emphasize the importance of general digital security awareness as well as smartphone training to increase smartphone security behavior.
Keywords: dospělí; general security orientation; Smartphone; Adult; důvěrnost informací; Computer Security; lidé; Aged, 80 and over; health belief model; perceived severity; smartphone security behavior; chytrý telefon; Aged; Confidentiality; motivace; self-efficacy; zabezpečení počítačových systémů; lidé středního věku; senioři nad 80 let; senioři; Middle Aged; Motivation; Humans